Nurses’ Knowledge, Attitudes, and Practices Regarding Sexually Transmitted Infection: A Comparison between Online and Group Education - Walaa Ali Alghrabat; Asieh Dehghani; Abdul Aziz Wannas Abd; Mahsa Sadat Mousavi (Future of Medical Education Journal, 2025)
Background: Sexually transmitted infections (STI) have numerous complications. Nurses can play a crucial role in educating people to prevent and treatment. This study aimed to compare the impact of online and group education on nurses’ knowledge, attitudes, and practices regarding STI.Method: This quasi-experimental study was conducted at Women and Children hospital in Diwaniyah, Iraq, in 2023. Pre-test and post-test were conducted using a questionnaire. Follow-up design was also performed. The participants were divided into two groups (n = 50/group) as a WhatsApp-based training program, and the group-based training by random allocation. Data were analyzed in SPSS 22 using repeated‑measures ANOVA, the Bonferroni correction, Kolmogorov-Smirnov, Levene’s tests, Fisher’s exact test, and Mann-Whitney U test.Results: The results showed that both groups had significant improvements in knowledge, attitude, and practice from before to after the intervention (p < 0.001). The group teaching group had significantly higher knowledge and attitude scores (19.80, 42.32) than the online teaching group (18.06, 39.00) (p = 0.008; p = 0.012). Both teaching methods were effective in improving practice scores.Conclusion: Both methods led to significant improvements in all three domains; however, the group-based method was more effective, particularly in improving knowledge and attitudes. Future research should also explore the long-term effects of hybrid models on learners’ competencies and patient outcomes.